Finding meaning after stroke: an analysis of older people’s stroke narratives - Ross, Susan Clare (The University of Edinburgh, 2011)
Little is understood about the process by which individuals maintain or lose a positive sense of wellbeing in the face of a chronic disabling condition such as stroke (Clarke, 2003). It appears that the impact of residual impairments and disabilities can pose significant problems for wellbeing in older adults, but the presence of such sequelae is not necessarily correlated with subjective wellbeing – some adapt well while others are devastated by minor sequelae (Clarke, 2003). Additionally, little is known about recovery in stroke survivors in relation to normal ageing processes (Green & King, 2007). Through narrative we bring a sense of order to the disorder in our lives, and gain a sense of temporal continuity as we define ourselves in the context of our experiences (Murray 2008). A qualitative study examined the narratives of a sample of six older people with stroke in the East of Scotland. Participants took part in an episodic interview exploring their experience of stroke and the impact it has had on them and their lives. Narrative analysis was used to explore these stories. A story analytic approach was used to examine the content and structure of stroke narratives. A performative analysis revealed that narrative anchors relating to health, relationships, activity and ageing were used by participants to make sense of stroke, while stroke itself was an anchor point in participants‟ ongoing life stories. These findings were interpreted in relation to theories of ageing, suggesting that a developmental approach may be helpful in understanding the experiences of stroke survivors entering frailty, rather than focussing on the active ageing strategies which benefit those in the younger-old age groups. An approach similar to that used in working with grief is proposed as a framework to help health and social care staff and service users understand the process of adjustment following stroke.
Keywords: stroke; older people; adjustment; narrative analysis; qualitative